BREASTFEEDING AND EARLY WEANING-ASSOCIATED FACTORS: INTEGRATIVE REVIEW: BREASTFEEDING AND EARLY WEANING-ASSOCIATED FACTORS: INTEGRATIVE REVIEW - Feitosa, Rebeca Maria Claudino; Santana, Carolina Moreira; Bezerra, Yuri Charllub Pereira; Quental, Ocilma Barros de (Brazilian Journal of Production Engineering, 2020)
Breastfeeding is arguably the ideal food for the child’s health and, consequently, for the mother’s health. Despite all the advantages that breast milk provides, early weaning is still prevalent in several countries, including Brazil, being affected by several factors, such as maternal characteristics, working conditions, socioeconomic situation, marital status and monitoring. Thus, this study sought to identify factors related to early weaning from breastfeeding, through an integrative literature review in databases Scientific Eletronic Library Online (SciELO) and Biblioteca Virtual de Saúde (BVS), in the years 2015 to 2019. Inclusion criteria were: full text articles, free online version, main subject, national and international productions. Studies repeated on databases and articles that did not answer the guiding question of the study were excluded. There was the selection of 25 articles, which showed several conditions related to the interruption of breastfeeding and the consequent early weaning, namely: woman’s return to the job market, complications related to breasts, beliefs, use of artificial nipples, introduction of new foods and even the lack of information by health professionals. Although breast milk is considered the ideal food, the execution of breastfeeding is a process that includes numerous factors. There is need to implement strategies aimed at promoting breastfeeding and contributing to reducing infant mortality morbidity.